The milankovitch fingerprint on the distribution and thickness of bedding-parallel veins (beef) in source rocks. (December 2020) - Ravier, Edouard; Martinez, Mathieu; Pellenard, Pierre; Zanella, Alain; Tupinier, Lucie
Abstract: Bed-parallel, mineralized fractures are common in source rocks and generally consist in mm to cm thick veins developed parallel to bedding known as beef or bedding-parallel veins. Considering they can form a dense network of mechanical discontinuities, the prediction of beef distribution is a major issue impacting shale reservoir production. Beef distribution is predominantly controlled by the lithological characteristics of source rocks and we here decipher the relation between mineralogical and chemical proxies controlled by orbital parameters and distribution of the beef along a Late Jurassic section of the well-known Vaca Muerta Formation source rock in the Neuquén Basin. Using multiple proxies collected along the beef-rich Huncal section, we show that Milankovitch cycles rule the mineralogical evolution and beef distribution in these organic-rich mudrocks. Cycles inferred from the statistical treatment of sedimentary (magnetic susceptibility, elemental and mineralogical ratios), biogenic (total organic carbon) and diagenetic (beef distribution and thickness) signals revealed indeed the influence of an astroclimatic fingerprint in sediments and on processes controlling mineralized fracture generation and distribution. The astroclimatic memory recorded in many source rocks worldwide is therefore envisaged as a suitable proxy for the prediction of mineralized fracture distribution. Graphical abstract: Image 1 Highlights: Times-series analyses on sedimentary proxies and diagenetic calcite veins (beef). Milankovitch cycles controlled detrital input and preservation of organic matter. Imprint of the Milankovitch cycles on the reccurence and thickness of beef. Initial climate forcing induces differential diagenesis and control beef distribution in source rocks.